Analisis Kelayakan Usaha Dupa di Tengah Pandemi Covid 19 Di Kabupaten Tabanan Ditinjau Dari Aspek Pemasaran Dan Aspek Keuangan - I Wayan Agustina Agustina; Ni Ketut Murdani; Ni Putu Andini Desiyanti Laksmi (CV ODIS, 2022)
The COVID-19 pandemic has had a tremendous impact and has the potential to threaten the sustainability of various business sectors. In addition to the problem of competition, businesses also have to face the company's internal problems. To avoid the obstacles that will be faced and the risks that may arise during the running of the business, it is necessary to conduct a business feasibility study. The purpose of this study was to determine the feasibility of MSMEs in Gunung Kawi fragrant incense in terms of non-financial and financial aspects. The research method used is descriptive quantitative through the help of the Microsoft Excel program. The results of study 1) from the non-financial aspect, the MSME business of Gunung Kawi Harum Incense is still categorized as still feasible to run but several things need to be evaluated and improved in marketing strategies related to promotional activities still relying on resellers and word of mouth strategies so that market share is absorbed is still limited, and still uses the basic ingredients of semi-finished cense, 2) from the financial aspect, it shows that the MSME business of Gunung Kawi Fragrant Incense is feasible to run. This can be seen from the NPV (Net Present Value) obtained > 0 and has a positive value of Rp. 2,030,577,166. The resulting IRR (Internal Rate of Return) value> commercial bank interest rate is 17.47%. The resulting payback period is < from the investment age, which is 3.2 years. The Profitability Index (PI) obtained > 1, which is 1.18.